Peran Keterampilan Dasar Mengajar dalam Mewujudkan Pembelajaran Efektif - Lidia Br Sinaga; Husnun Nabila; Cut Kumala Sari (Lembaga Pengembangan Kinerja Dosen, 2025)
This research aims to comprehensively analyze the Basic Teaching Skills (KDM) that are crucial for teachers in supporting the learning process. Through a literature study, this research examines various views and literature related to skills that teachers must have, such as opening and closing lessons, explaining material, leading discussions, asking questions, providing reinforcement, and creating variations in learning. The research findings show that basic teaching skills are not only related to the delivery of material, but also include the teacher's ability to arouse interest, increase motivation, and encourage active student involvement. A thorough and integrated application of these skills can contribute to improving the quality of teaching as well as students' learning outcomes.